Design, synthesis, in vitro anticancer evaluation, kinase inhibitory effects, and pharmacokinetic profile of new 1,3,4-triarylpyrazole derivatives possessing terminal sulfonamide moiety - Abdel-Maksoud, Mohammed S.; El-Gamal, Mohammed I.; El-Din, Mahmoud M. Gamal; Oh, Chang Hyun (TAYLOR & FRANCIS LTD, 2019)
The present work describes the design and synthesis of a novel series of 1,3-diaryl-4-sulfonamidoarylpyrazole derivatives 1a-q and 2a-q and their in vitro biological activities. The target compounds were evaluated for antiproliferative activity against NCI-60 cell line panel. Compounds 1c, 1g, 1k-m, 1o, 2g, 2h, 2k-m, 2o, and 2q showed the highest mean inhibition percentages at 10 mu M single-dose testing and were selected to be tested at 5-dose mode. The ICs50 of the most potent compounds were determined over the 60 cell lines. Compound 2l exhibited the strongest activity against different cell lines with IC50 0.33 mu M against A498 renal cancer cell line. Compound 2l was tested over a panel of 20 kinases to determine its molecular target(s), and its IC50 values over the most sensitive kinases were defined. In vitro stability and in vivo pharmacokinetic profile of compound 2l was also investigated.
Keywords: MELANOMA-CELL LINE; ANTIPROLIFERATIVE ACTIVITY; RAF KINASE; CANCER; DIARYLAMIDES; DIARYLUREAS; SCAFFOLD; SERIES